The Relationship of Chronic Pain to Attitudes Toward Sucide and Physician-Assisted Suicide among Latino and Non Hispanic White Elders - Rubén O. Martinez; Olga J. Santiago; David V. Espino; Daniel Vélez Ortiz (Journal of Palliative Care And Hospice, 2017)
The objective of this study was to examine differences between Latino and White older adults in attitudes toward suicide and physician-assisted suicide in chronic pain scenarios. We used a cross sectional study design at four outpatient care sites in San Antonio, Texas. The study sample included 204 subjects (106 Whites and 98 Latinos), 60 years of age and older, with Mini Mental State Examination scores of 24 or higher. No statistically significant between ethnic group differences in attitudes toward suicide or physician-assisted suicide in chronic pain scenarios were found. However, separate analyses by ethnic group showed that the factors associated with these attitudes differed between ethnic groups, with attitudes among Whites significantly and negatively associated with religiosity and those among Latinos significantly and positively associated with depression, while acculturation was significantly and negatively associated with attitudes toward physician-assisted suicide in chronic pain scenarios. This study’s findings suggest that depression and acculturation among Latino elders and religion among White elders are determinant factors of these attitudes in chronic pain, end-of-life scenarios. Further research is needed with more heterogeneous study samples, including Latino subgroups (e.g. Mexican Americans, Puerto Ricans, Cubans) and more diverse ethnic groups in terms of socioeconomic status and educational level characteristics.
Keywords: End of life